Characterization and comparative transcriptome analyses of Salmonella enterica Enteritidis strains possessing different chlorine tolerance profiles. (1st November 2022) - Wang, Wensi; Xiao, Xingning; Wang, Hongxun; Wang, Sheng; Xiao, Yingping; Yang, Hua; Hou, Wenfu; Wang, Wen
Abstract: We compared viability, morphology, enzyme activity and gene expression patterns between the chlorine tolerant S. Enteritidis RE 13 and the sensitive strain S. Enteritidis CVCC1806. As expected, viability of strain CVCC1806 was significantly lower than for RE 13 after exposure to 100 mg/L NaClO for 20 min and the sensitive strain displayed severe cell membrane damage and intracellular ATP depletion compared with the tolerant strain. The NAD + /NADH ratios for the sensitive vs tolerant strain were also significantly ( p  < 0.05) different (3.59 ± 0.95 vs. 0.88 ± 0.47) and indicated that tolerance included adaptation to redox perturbations. Transcriptomes of these two strains following chlorine exposure identified significant up-regulation of efflux pump systems ( proV/W, OmpF, marA ), oxidative stress response ( trxC, yhhP, soxS ) and DNA repair ( dnaQ, polB, yaiV ) for the tolerant RE 13 strain. These data indicated that S. Enteritidis RE 13 has a more robust response to oxidative stress that acted to maintain its intracellular redox balance to adapt and survive in the presence of chlorine. Noteworthy, the operon gene cluster of the bacterial microcompartment PDU were up-regulated about 64-fold in tolerant strain RE 13 compared with the sensitive strain, posing a more serious threat to human intestinal health. Highlights: The tolerant strain kept viability and membrane integrity under chlorine stress. Transcriptome response between chlorine tolerant and sensitive strain was compared. Multiple efflux pumps were triggered by NaClO, leading to chlorine resistance. Pdu operon was upregulated in tolerant strain that may be more pathogenic.